Radiation-Inactivated S. gallinarum Vaccine Provides a High Protective Immune Response by Activating Both Humoral and Cellular Immunity - Ji, Hyun Jung; Byun, Eui-Baek; Chen, Fengjia; Ahn, Ki Bum; Jung, Ho Kyoung; Han, Seung Hyun; Lim, Jae Hyang; Won, Yongkwan; Moon, Ja Young; Hur, Jin; Seo, Ho Seong (Frontiers in Immunology, 2021)
Salmonella enterica subsp. enterica serovar Gallinarum (SG) is a common pathogen in chickens, and causes an acute systemic disease that leads to high mortality. The live attenuated vaccine 9R is able to successfully protect chickens older than six weeks by activating a robust cell-mediated immune response, but its safety and efficacy in young chickens remains controversial. An inactivated SG vaccine is being used as an alternative, but because of its low cellular immune response, it cannot be used as a replacement for 9R. In this study, we employed gamma irradiation instead of formalin as an inactivation method to increase the efficacy of the inactivated SG vaccine. Humoral, cellular, and protective immune responses were compared in both mouse and chicken models. The radiation-inactivated SG vaccine (r-SG) induced production of significantly higher levels of IgG2b and IgG3 antibodies than the formalin-inactivated vaccine (f-SG), and provided a homogeneous functional antibody response against group D, but not group B Salmonella. Moreover, we found that r-SG vaccination could provide a higher protective immune response than f-SG by inducing higher Th17 activation. These results indicate that r-SG can provide a protective immune response similar to the live attenuated 9R vaccine by activating a higher humoral immunity and a lower, but still protective, cellular immune response. Therefore, we expect that the radiation inactivation method might substitute for the 9R vaccine with little or no side effects in chickens younger than six weeks.